Influence of Chinese Culture on the Development of Mosques in Indonesia - H T Fachrudin; I F Pane; P S Pane (Jurnal Scientia, 2021)
Islam in Indonesia is experiencing a history and cultural development that is quite unique. Where in the history of the spread of Islam in Indonesia began in 1389. During the era of the leadership of the Kingdom of Majapahit, many majapahit areas were released, so Majapahit owed the Ming Dynasty from China, because at that time many kingdoms were controlled by China. It was at this time that Admiral Cheng Ho sailed to the archipelago and performed Islamic shiar in Java. Ethnic Cina is an ethnicity that is able to maintain its existence. Seen from the ornaments they use on the buildings they build, ranging from colors and ornaments of typical Chinese shapes. This is as a form of their identity and as a sign of the territorythey live in to influence the existence of mosque architecture. Until now Arsitektur Cina is still seen invariousmosques in Indonesia, asa form of respect for the ancestors of branda who have spread shiar Islam or asa beto unite the communityantara Muslim Chinese.